Audience formation: a view at cultural institutions and contemporary art (Revista Apotheke, 2021)
The article intends to comprehend how the issue of audiences is set in cultural institutions nowadays. Therefore, it discusses the importance of shared experience for the aesthetic experience, the role of cultural mediation in this process, the museum as a privileged place for this type of experience and the notion that the presence of diverse audiences is vital for sustainability and survival of the art world(s). Thus, which contemporary strategies have beenadopted for the production of new audiences? A case study of the activation “Descoloração Global” (Global Bleaching), proposed by the artist Maxwell Alexandre during his solo exhibition “Pardo é Papel” (Pardo is Paper), at the Museu de Arte do Rio, in 2020, can giveanswers to possible transformations in the way we establish and address art and culture.
Keywords: audiences; culutral institutions; contemporary art